INTERPRETASI FASĀD DAN EKSPLOITASI SUMBER DAYA ALAM (ANALISIS SEMANTIK TOSHIHIKO IZUTSU TERHADAP Q.S. AR-RUM AYAT 41) - Tarto, Tarto; Uswah Azizah, Nabila; Suyuti, Muh Hikamudin (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2025)
The global environmental crisis, characterized by massive deforestation and ecosystem degradation, has reached an alarming level, including in Indonesia. This research aims to uncover the profound meaning of the term fasād (corruption/damage) in QS. Ar-Rum verse 41 through Toshihiko Izutsu's semantic approach and to analyze its relevance to contemporary natural resource exploitation phenomena. The methodology used is library research with descriptive-analytical analysis. The findings indicate that, fundamentally, fasād means damage or a condition that deviates from balance. Relationally in the Qur'an, fasād is closely associated with the concepts of injustice (ẓulm), transgression, and the neglect of the trust of vicegerency (khilāfah). Its relevance to current natural exploitation includes acts of forest destruction, irresponsible mining, and waste pollution, all of which are tangible manifestations of human hands disturbing the balance of Allah's creation. This research concludes that addressing the ecological crisis requires spiritual transformation and the application of environmental ethics based on Qur'anic values.